REGENERASI LINGKUNGAN CINA BENTENG DI JALAN CILAME - Valeria Kristi; Timmy Setiawan (Jurusan Arsitektur dan Perencanaan, 2023)
The district area of Tangerang Lama Town is a Chinese suburban area that became the root of Tangerang City. It is a historical site for the Cina Benteng culture. Tangerang Lama itself is a cultural destination but some of the area is abandoned and left degraded. The